2023
DOI: 10.1002/pat.5990
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the recent advances in flame retarded poly(lactic acid)

Abstract: Poly(lactic acid) (PLA) is derived from crops, and has a broad application prospect in electronics and electrical, automotive industries due to its biodegradability and good physical and mechanical properties. However, PLA's flammability and serious melt dripping cannot meet the requirements of terminal products, thus limiting its application. Over the past decade, much research on flame retardant PLA has emerged. This paper reviews the development of PLA flame retardants in recent years, focusing on phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 181 publications
0
7
0
Order By: Relevance
“…6,27 Generally, the addition of excess flame retardants to PLA improves the flame retardancy but degrades the mechanical properties. 27 Figure 4 demonstrates the effect of various types and amounts of flame retardants on the mechanical characteristics of PLA composites. As shown in Figure 3a,b, with a loading of 10 wt % A-MBC/PA/A-TiO 2 as the flame retardant, the tensile, bending, and impact strengths of PLA/10AM increase, and the same enhancement trend is observed for PLA/10AM with 10 wt % A-MBC and PLA/ 10AT with 10 wt % A-TiO 2 .…”
Section: Characterization Of Flame Retardantsmentioning
confidence: 99%
“…6,27 Generally, the addition of excess flame retardants to PLA improves the flame retardancy but degrades the mechanical properties. 27 Figure 4 demonstrates the effect of various types and amounts of flame retardants on the mechanical characteristics of PLA composites. As shown in Figure 3a,b, with a loading of 10 wt % A-MBC/PA/A-TiO 2 as the flame retardant, the tensile, bending, and impact strengths of PLA/10AM increase, and the same enhancement trend is observed for PLA/10AM with 10 wt % A-MBC and PLA/ 10AT with 10 wt % A-TiO 2 .…”
Section: Characterization Of Flame Retardantsmentioning
confidence: 99%
“…Over the past few decades, researchers have been actively working on mitigating the flammability of PLA through the development of flame retardants or intrinsically flame-retardant PLA. 5,6 Phosphorus flame retardants (PFR) draw more and more attention to improve the flame retardancy of polymers for their more environmentally friendly and higher efficiency compared to the traditional halogen and inorganic flame retardants. 7,8 According to the different flame-retardant methods, it can be divided into gas phase flame retardant and condensed phase flame retardant.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to most of plastics, PLA is intrinsically flammable, which greatly limits its applications. , It has been found that PLA has a limiting oxygen index (LOI) of only 18.0–21.0%, , which is a flammable grade, and has no burn rating in vertical burn tests with a large amount of molten droplet generation. Over the past few decades, researchers have been actively working on mitigating the flammability of PLA through the development of flame retardants or intrinsically flame-retardant PLA. , …”
Section: Introductionmentioning
confidence: 99%
“…Ammonium polyphosphate (APP) is widely used because of its good thermal stability, low price, low toxicity, and high flame-retardant performance. [21][22][23][24] However, when APP is used alone, its compatibility with PLA and charring effect is poor.…”
Section: Introductionmentioning
confidence: 99%